Cryptic excess argon in metamorphic biotite: Anomalously old 40Ar/39Ar plateau dates tested with Rb/Sr thermochronology and Ar diffusion modelling. (15th December 2021) - Scibiorski, E.; Jourdan, F.; Mezger, K.; Tohver, E.; Vollstaedt, H.
Abstract: In 40 Ar/ 39 Ar geochronology, excess Ar is 40 Ar that does not derive from the in situ radioactive decay of 40 K, or from the measurable input of atmospheric Ar, and results in increased daughter-parent ratios that correspond to anomalously old apparent dates without geological age significance. Excess 40 Ar is commonly identified by a saddle-shaped 40 Ar/ 39 Ar degassing spectrum. However, biotite from the east Albany-Fraser Orogen of Western Australia contains excess 40 Ar, but yields well-defined 40 Ar/ 39 Ar plateau dates, reproducible upon replicate analysis of biotite from the same sample. This "cryptic excess 40 Ar" is inferred where plateau dates (1) are older than existing time constraints on cooling, such as U/Pb zircon ages for amphibolite to granulite facies metamorphism, and (2) vary between multiple samples from the same outcrop that have experienced the same thermal history. Rb/Sr geochronology is used to test the geologic significance of 40 Ar/ 39 Ar plateau dates, as the closure temperatures of both chronometers are similar, and the two chronometers are expected to yield similar cooling dates in an undisturbed system. Six Rb/Sr biotite-whole rock isochron ages from three outcrops yield a weighted mean age of 1133 ± 3 Ma (MSWD = 1.13, P = 0.34), and are interpreted to record post-orogenic cooling. 40 Ar/ 39 Ar plateau dates from the same samples are 31–394 Ma older, and in six of nine samples cannot be explained by simple monotonic cooling, by low-temperature biotite recrystallisation, or by alteration; instead, biotite contains cryptic excess 40 Ar. Diffusion modelling of 40 Ar/ 39 Ar step-heating plateaus suggests that Ar, both excess and radiogenic, is homogeneously distributed within the crystal lattice, and was incorporated during biotite crystallisation. Biotite likely crystallised in a rock with a high partial pressure of Ar, possibly due to a high rate of radiogenic 40 Ar generation in a K-rich lithology, together with a poorly-connected intergranular fluid network that inhibited Ar loss from the rock volume. This is supported by a homogeneous distribution of Ar at the cm scale, with reproducible biotite 40 Ar/ 39 Ar dates from each sample. Patchy fluid circulation during metamorphism led to the pervasive but heterogeneous distribution of excess 40 Ar across outcrops. Due to the presence of the 40 Ar/ 39 Ar plateau, cryptic excess 40 Ar is difficult to identify a priori, without comparison to additional geochronological constraints. Where cryptic excess 40 Ar on a regional scale has been identified, such as in the eastern Biranup Zone of the Albany-Fraser Orogen, Rb/Sr geochronology may provide a more robust alternative to constrain the cooling path of rocks from high temperatures.